Slovanska podoba Besede - Zajc, Neža (ZRC SAZU, Založba ZRC, 2012)
The monograph ('The Slavic image of word : the forces of depiction in a Slavic language of the sixteenth century') sets the groundwork for the elucidation of some historical development in the middle of the evolution of Slavic languages that also influenced the establishment of literary language both in Slovenia and Russia in the mid-sixteenth century (the beginning of Slavic literary and liturgy, the intertwining of Greek and Latin Christian linguistic patterns, connection to the East-West Schism in 1054).